OPTIMALISASI PENINGKATAN KINERJA KARYAWAN MELALUI FLEKSIBILITAS KERJA, KOMPENSASI, DAN MOTIVASI KERJA - Ida Ayu Putu Widani Sugianingrat; I Wayan Vienna Putra; Putu Yudy Wijaya (UNHI Press, 2026)
A company's success is largely determined by employee performance, as they are a key element in implementing strategy and day-to-day operations. High-performing employees are able to complete tasks efficiently, innovate in finding solutions, and contribute to achieving company goals. Essentially, many factors can influence employee performance. However, based on field observations, the most frequent complaint from employees is the level of freedom or flexibility the company provides in carrying out their duties. Compensation is also a key employee complaint; many employees still feel that the compensation provided by the company is not optimal, believing that the company could actually provide more than what they currently receive. Work motivation can be used as a mediator to mediate the relationship between work flexibility and compensation on employee performance. The purpose of this study was to determine the effect of work flexibility and compensation on employee performance, with work motivation as a mediating variable. The data used were primary and secondary data obtained through questionnaire distribution. The sample size used in this study was 85 respondents. The data collection technique was carried out in the form of a questionnaire. The data analysis technique used Partial Least Squares (PLS). The results of this study indicate that work flexibility does not have a significant effect on employee performance. Compensation has a positive and significant effect on employee performance. Work flexibility does not have a significant effect on work motivation. Compensation has a positive and significant effect on work motivation. Work motivation has a positive and significant effect on employee performance. Work flexibility does not have a significant effect on employee performance with work motivation as a mediating variable. Compensation does not have a significant effect on employee performance with work motivation as a mediating variable.